Phytochemical Screening and Antibacterial Activity of Libyan Globularia alypum - Suad Shanab; Basma Doro; Abdulruzag Auzi (Khalij-Libya Journal of Dental and Medical Research, 2021)
Aims. The aim of this study was to assess the phytochemical screening and antibacterial effect of the aerial parts of G. alypum cultivated in Libya. Methods. The methanolic extract of G. alypum (at concentrations 100 mg/ml, 300 mg/ml, 500 mg/ml and 700 mg/ml) were tested against 13 different strains of standard bacteria (ATCC) by four different methods; paper disc diffusion method, well diffusion method, broth dilution method and finally study the effect of extract on growth curve of bacterial cell were studied. Results. The results of phytochemical screening revealed the presence of flavonoids, phenols, reducing sugars, tannins, saponins, coumarins, steroids, terpenoids, carotenoids, antraquinones and glycosides. While the results of antibacterial tests showed remarkable inhibition of the bacterial growth, with maximum inhibition on growth of Methicillin Resistant Staphylococcus aureus (MRSA) and Staphylococcus aureus. Moderate effect on growth of Enterococcus faecalis, Bacillus subtilis, Aeromonas hydrophila and Salmonella poona. While, the lowest inhibition showed in Yersinia enterocolitica and Listeria monocytogenes. However, the extract did not have any effect on Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella typhimurium and Klabsiella pneumonia. Conclusion. The methanolic extract of Globularia alypumaerial parts contain the most important constituents with positive results during phytochemical screening, and have antibacterial activity against gram positive and gram-negative bacteria.